Relations Between the Writers’ Associations of Kosova and Serbia in the Second Half of the 1980s - Mehmeti Arban (Comparative Southeast European Studies, 2021)
The author examines the activities and relations between the writers’ associations of Kosova and Serbia during the second half of the 1980s. He focuses on the interaction between the two cultural institutions and the debates they organized between the mid-1980s and the end of the decade. While political relations were deteriorating, the meetings of the two associations were intended to form a channel for communication which it was hoped would stimulate debate among intellectuals about then-current relations between Kosovar-Albanians and Serbs. But, as this study explains, those attempts ended in endless disagreements over “historical truths.”